2022
DOI: 10.1029/2022gl100590
|View full text |Cite
|
Sign up to set email alerts
|

Influence of African Easterly Wave Suppression on Atlantic Tropical Cyclone Activity in a Convection‐Permitting Model

Abstract: Understanding the physical controls on tropical cyclone (TC) frequency represents a major challenge, as there is no theory to explain why the global annual number of TCs is relatively constant in historical observations and no consensus on future changes in TC frequency (Sobel et al., 2021). Pre-existing low-pressure disturbances, or TC "seeds," may trigger TC genesis, and have been identified as one possible factor in determining TC frequency. The typical Atlantic TC seed is provided by African easterly waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…AEWs are synoptic‐scale disturbances that propagate along the African easterly jet (AEJ) in two tracks north and south of ∼15°N and grow off of the baroclinic‐barotropic instability of the AEJ (Burpee, 1972; Pytharoulis & Thorncroft, 1999). Recently, the relationship between AEWs and TCs has been called into question, with regional climate model data indicating that suppressed AEW activity did not affect basin‐wide Atlantic TC frequency (Danso et al., 2022; Patricola et al., 2018). The AEW‐TC relationship is further complicated by the potential effects of anthropogenic climate change, where studies have shown that climate change may double the economic damages of TCs by the year 2100 through increased TC intensity, precipitation, and storm surge (Knutson et al., 2020; Mendelsohn et al., 2012; Patricola & Wehner, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…AEWs are synoptic‐scale disturbances that propagate along the African easterly jet (AEJ) in two tracks north and south of ∼15°N and grow off of the baroclinic‐barotropic instability of the AEJ (Burpee, 1972; Pytharoulis & Thorncroft, 1999). Recently, the relationship between AEWs and TCs has been called into question, with regional climate model data indicating that suppressed AEW activity did not affect basin‐wide Atlantic TC frequency (Danso et al., 2022; Patricola et al., 2018). The AEW‐TC relationship is further complicated by the potential effects of anthropogenic climate change, where studies have shown that climate change may double the economic damages of TCs by the year 2100 through increased TC intensity, precipitation, and storm surge (Knutson et al., 2020; Mendelsohn et al., 2012; Patricola & Wehner, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) and Danso et al. (2022) used a regional climate model to examine the AEW‐TC relationship by comparing ensembles of simulations where AEWs were either prescribed or removed through the lateral boundary conditions. Both studies found that suppressed AEW activity did not affect basin‐wide Atlantic TC frequency (Danso et al., 2022; Patricola et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations